Acylated flavonoid glycosides from Barringtonia racemosa. Issue 9 (2nd May 2020) - Van, Quach Thi Thanh; Vien, Le Thi; Hanh, Tran Thi Hong; Huong, Phan Thi Thanh; Cuong, Nguyen The; Thao, Nguyen Phuong; Thuan, Nguyen Huy; Dang, Nguyen Hai; Thanh, Nguyen Van; Cuong, Nguyen Xuan; Nam, Nguyen Hoai; Kiem, Phan Van; et al.
Abstract: Using various chromatographic separations, three new acylated flavonoid glycosides, namely barringosides G–I (1 –3 ), were isolated from the water-soluble extract of Barringtonia racemosa branches and leaves. The structure elucidation was performed by extensive analysis of the 1D and 2D NMR and HR-QTOF-MS data. Of the isolated compounds, barringoside I (3 ) showed moderate inhibitory effects on LPS-induced NO production in RAW264.7 cells with an IC50 of 52.48 ± 1.04 µM. Graphical Abstract: